Optimum Ratio of Fresh Manure and Grain Size of Phosphate Rock Mixture in a Formulated Compost for Organomineral NP Fertilizer - Nugroho, Sutopo Ghani; Dermiyati, .; Lumbanraja, Jamalam; Triyono, Sugeng; Ismono, Hanung; Sari, Yosa Triolanda; Ayuandari, Elva (JOURNAL OF TROPICAL SOILS, 2012)
The objective of multi years study was to formulate an alternative organic based fertilizer by mixing a fresh manureand phosphate rock with several different grain sizes conducted in the Field Experimental Station of the Universityof Lampung. Both materials of the fresh manure and phosphate rock were obtained from local sources. Five levelsof mixture of fresh manure and phosphate rock, three levels of grain size of phosphate rock, and two kinds ofcomposting technique were factorial set up. The mixture materials were aerobically composted for 12 weeks. Theresults of the first year study show that (a) the optimum ratio of the mixture of fresh manure and phosphate rock was80% to 20% with the optimum of grain size of phosphate rock < 3 mm; (b) 6-8 weeks of incubation of the mixturematerials has been optimally composted under aerobic conditions of the complete mixture of batch compostedtechnique; (c) the quality of the final produced compost was considered to fulfill the requirement of standard criteriaof organic fertilizer; while (d) the quantity of compost recovered up to 75.07% which was a reliable quantity of massproduction of organic fertilizer.[How to Cite: Nugroho SG, Dermiyati, J Lumbanraja, S Triyono, H Ismono, YT Sari and E Ayuandari. 2012. Optimum Ratio of Fresh Manure and Grain Size of Phosphate Rock Mixture in a Formulated Compost for Organomineral NP Fertilizer. J Trop Soils 17 (2) : 121-128. Doi: 10.5400/jts.2012.17.2.121][Permalink/DOI: www.dx.doi.org/10.5400/jts.2012.17.2.121]